2011
DOI: 10.2478/s11658-011-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol promotes cell proliferation in rat osteoarthritis model chondrocytes via PI3K/Akt pathway

Abstract: Osteoarthritis (OA) is the most common cause of musculoskeletal pain and disability. The importance of chondrocytes in the pathogenesis of OA is unequivocal. 17β-estradiol (E2) has a potential protective effect against OA. However, the mechanism of E2 in OA chondrocytes remains unclear. In this study, we investigated the regulative effect of E2 on cell growth and the relationship between E2 and the PI3K/Akt pathway in rat OA model chondrocytes (pretreated with interleukin-1β). We found that E2 induced chondroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 51 publications
1
72
0
1
Order By: Relevance
“…Therefore, the functional changes of chondrocytes play an important role by contributing to the degradation of the articular cartilage and thus to the pathogenesis of OA (15,16). Several studies have reported that there is a very low proliferative activity in osteoarthritic chondrocytes, which might be an efficient treatment to cure or even delay the progression of OA by promoting chondrocyte proliferation (17,18). Therefore, the present study has focused on chondrocyte proliferation and extends the clinical observations of the potential anti-cartilage degenerative effect of millimeter waves and establishes a scientific foundation for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the functional changes of chondrocytes play an important role by contributing to the degradation of the articular cartilage and thus to the pathogenesis of OA (15,16). Several studies have reported that there is a very low proliferative activity in osteoarthritic chondrocytes, which might be an efficient treatment to cure or even delay the progression of OA by promoting chondrocyte proliferation (17,18). Therefore, the present study has focused on chondrocyte proliferation and extends the clinical observations of the potential anti-cartilage degenerative effect of millimeter waves and establishes a scientific foundation for further research.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptosis of chondrocytes is widely considered to play a crucial role in the pathogenesis of OA [8]. Bone marrow-derived mesenchymal stem cells (BMSCs) possess pluripotency during several passages, and are commonly acceptable for differentiation into many cell types, such as chondrocytes and osteoblasts [9-11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the functional changes of chondrocytes play an important role by contributing to the degradation of articular cartilage and thus to the pathogenesis of OA (27,28). Several studies have reported that osteoarthritic chondrocytes have a very low proliferative activity; thus, promoting chondrocyte proliferation may be an efficient treatment strategy to cure or delay the progression of OA (29,30). Therefore, in the present study, we focused on chondrocyte proliferation and the anti-degenerative effects of DHJSD on cartilage.…”
Section: Discussionmentioning
confidence: 99%